A Path Analysis to Identify Factors Influencing the Provision of Water in Addition to Breast Milk by Mothers of Infants under Six Months of Age in Conakry and Kindia Regions, Republic of Guinea - Ninamou, Nèmanan R.; Dupuis, Jérémie B.; Zagré, Noël-Marie; Daffé, Mamady; Blaney, Sonia (International Journal of Child Health and Nutrition, 2021)
Water provision to infants under six months of age (IU6M) can hamper exclusive breastfeeding (EBF). Understanding factors and their relationships influencing this practice is needed to tailor EBF promotion programs. Using a validated questionnaire, this study aims to identify pathways in which individual factors and the environment interact to affect the provision of water in addition to breast milk among 300 mothers of IU6M. Our finding shows that 75% of mothers intended to provide water in addition to breast milk to their IU6M and that about 60% reported doing it. Results of the final path show that the subjective norm/SN (β = 0.432, p < 0.001), the attitude (β = 0.349, p < 0.001), and to a lesser extent the perceived control/PC (β = 0.141, p = 0.005) predict the intention of mothers to provide water in addition to breast milk to their IU6M. The environment scores predict the attitude (β = 0.210, p = 0.001) and the SN (β = 0.284, p < 0.001). Having the mother practicing early breastfeeding initiation at birth positively predicted the PC score (β = 0.157, p = 0.017) and predicted an increasing score of SN (β = 0.221, p = 0.003). Even though predicting the final behavior is complex, this research provides directions to nutrition education programs to tailor their content to the context and be more efficient in reducing the proportion of women providing water to their IU6M, hence contributing to the improvement of EBF.